(untitled) (Security Dialogues, 2024)
The General Assembly of the United Nations adopts Resolution on Srebrenica Genocide on 23 May 2024, designating 11 July as the „International Day of Reflection and Commemoration of the 1995 Genocide in Srebrenica“. The Resolution on Srebrenica Genocide was adopted by a vote of 84 in favour to 19 against, with 68 abstentions. One of the objectives of adopting the Resolution on Srebrenica Genocide is to condemne any denial of Srebrenica genocide and actions that glorify those convicted of war crimes, crimes against humanity and genocide by international courts. The adoption of the Resolution on Srebrenica Genocide resonates in the region of the Western Balkans, but also far beyond its borders. Part of the statements that preceded the adoption of the Resolution on Srebrenica Genocide and that appeared in public after its adoption may exacerbate tensions, and even existence of Bosnia and Herzegovina. Aim of this paper is to analyze the statements and narratives relate to Resolution on Srebrenica Genocide and put it in the context of the current political and security situation in Bosnia and Herzegovina. Does the adoption of the Resolution on Srebrenica Genocide lead to further reconciliation of the people in Bosnia and Herzegovina? Will there be a review of the conflicts of the last century in Western Balkan region after this?